Affect in Art Education: Spinoza, Deleuze and Guattari and the Emerging Creative Subject - Boberg, Ingrid (Auckland University of Technology, 2018)
This research explores the relationship between art pedagogy and art practices of the emerging creative subject in the art school studio. The significance of this research is in its contemplation of how art education “functions more as an idea of education” (Groys, 2009, p. 27). The “unspecificity” of art pedagogy enables students to utilise individual and personalised capabilities to create innovative, and novel methodologies and methods for the development of an art practice. The “studio” is conceptualised as an environment for working/exploring/learning that is unfettered by the constraints of more traditional learning environments. In this milieu, the art school lecturer acts as incumbent and facilitator, holding the space and providing subtle direction. One of the core contributions of this study is in locating Barach Spinoza’s concepts within art education (specifically the art critique), and its use of Gilles Deleuze and Felix Guattari’s notion of rhizomatic thinking to substantiate methodologies and methods in art-making: where embracing an intuitive practice, and forgoing pre-conceived outcomes becomes essential to the unfolding of a student’s knowledge and ethical understanding. The emerging creative subject is positioned as generator, performer, witness, beneficiary and student within the art school studio milieu. I explore how the studio milieu enables learning through affective negotiation and response. These affective responses within the art encounter, in turn connect with new and expanding conceptual territories. This encompasses the generation and presentation of the artwork and the ensuing art critique. In this respect, I examine how new experience translates into knowledge, where percept, affect and concept interact to generate conceptual-contextual understanding for the student. I explore how studio facilitates such interactions, and how in the process normative hegemonies dissolve into a state of provisionality. This occurs because difference is continuously emerging in practice and in perception. The thesis utilises theories and philosophy of Spinoza, Deleuze, and Guattari to frame pedagogical processes, events and behaviours conducive to the processes of “becoming” of the subject within the context of the studio. It looks at the functionality, connectivity and productivity associated with studio life, highlighting the importance of the body and mind working in unison as meaning is made from the art encounter. The recognition and appreciation of the body as intelligence has influenced a turn towards Spinozist theories and the affectual capability of the body in relation to art pedagogy and becoming-artist. The thesis explores how affective encounters provide opportunity for the development of ideas that not only belong to an art practice, but are also part of the processual acts belonging to subjectivity and individuation. I discuss the processes that may occur for the art student as dynamic experiences applicable to creative practice including: emergence, provisionality, contingency, tendency, change, and difference. This is encouraged by prompting ethical and empathic thinking through the conscious expansion of what Spinoza (1996) calls “inadequate ideas” into “more adequate ideas”. This thesis adopts a methodology that, like the processes occurring within the art school studio, draws on intuition and rhizomatic movement in conjunction with appetite to shape and forge the argument that affect is imperative to art education.
Keywords: Affect; Spinoza; Deleuze and Guattari; Art pedagogy; Art critique; Ethics